Depression in young adults is associated with increased carotid atherosclerotic burden: insights from the Corinthia study. (25th November 2020) - Theofilis, P; Oikonomou, E; Vogiatzi, G; Lazaros, G; Tsalamandris, S; Mystakidi, V.C; Goliopoulou, A; Fountoulakis, P; Miliou, A; Chasikidis, C; Tousoulis, D
Abstract: Introduction: Depression appears to have a detrimental effect not only on mental health but also in the progression of various diseases. Purpose: The examination of a potential association between depression and atherosclerosis progression in a rural population. Methods: In the context of the cross-sectional Corinthia study, volunteers fulfilled a questionnaire concerning emotional health. The Geriatric Depression Scale was used for individuals aged 60 or more while the Zung self-rating depression score was preferred in younger adults. Carotid ultrasonography examination was performed to evaluate the mean carotid intima-media thickness (cIMT). Thickness of cIMT>1.5 mm or protrusion >50% compared to adjacent segments was considered as atherosclerotic plaque. Results: Young adults with significant depression were usually female and did not differ significantly on other risk factors of atherosclerosis compared to those with mild or no depressive disorder. Importantly, those with moderate-severe depression appeared to have increased mean cIMT (Mild-No depression: 0.85±0.30mm, Moderate-severe depression: 0.91±0.42mm, p=0.04) and a higher carotid plaque burden (Mild-No depression: 12.8%, Moderate-severe depression: 20.3%, p=0.04). With regards to the elderly, those with moderate-severe depression were usually smokers (Mild-No depression: 13.9%, Moderate-severe depression: 24.2%, p=0.01). However, mean cIMT (Mild-No depression: 1.11±0.47mm, Moderate-severe depression: 1.09±0.39mm, p=0.69) and carotid plaques (Mild-No depression: 31.1%, Moderate-severe depression: 36.1%, p=0.36) did not differ according to depression status in this subgroup. Conclusion: Significant depressive disorder is associated with accelerated carotid atherosclerosis in young individuals. Funding Acknowledgement: Type of funding source: None